2006
DOI: 10.1007/s00418-006-0238-6
|View full text |Cite
|
Sign up to set email alerts
|

DNAse I pre-treatment markedly enhances detection of nuclear cyclin-dependent kinase inhibitor p57Kip2 and BrdU double immunostaining in embryonic rat brain

Abstract: As a member of the CIP/KIP family of cyclin-dependent kinase inhibitors (CKIs), p57Kip2 binds tightly to G1 cyclin/cyclin-dependent kinase complexes to block cell cycle progression. CKIs play critical roles in regulating the transition from proliferation to differentiation in many tissues, including the nervous system. Conversely, CKI dys-regulation contributes to neoplasia and cancer progression. While the combined detection of CKI immunoreactivity and S phase entry using bromodeoxyuridine (BrdU) incorporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…29 A similar selective additive effect has been shown for DNAse treatment to enhance the detection of nuclear antigens. 30,31 We tried TCEP as a substitute for 2-ME and we showed that it can be an alternative which works at a much lower molar ratio than 2-ME. At 1 mM the cost is, however, 5-fold.…”
Section: Discussionmentioning
confidence: 98%
“…29 A similar selective additive effect has been shown for DNAse treatment to enhance the detection of nuclear antigens. 30,31 We tried TCEP as a substitute for 2-ME and we showed that it can be an alternative which works at a much lower molar ratio than 2-ME. At 1 mM the cost is, however, 5-fold.…”
Section: Discussionmentioning
confidence: 98%
“…To overcome the common problem that the pre-treatment of sections required for intense BrdU labeling severely compromises general nuclear staining (Tang et al, 2007), we developed a protocol based on the mild digestion of double-stranded DNA with DNase I (Ye et al, 2007). In this optimized triple-labeling protocol, free-floating sections were first incubated in 2 N HCl for 20 minutes and rinsed for 4 × 10 minutes in SPB.…”
Section: Sectioning and Immunocytochemistrymentioning
confidence: 99%
“…Therefore, we suggest that if the antigen is adjacent to the DNA-binding domain, it may be naturally exposed so that it can easily bind to antibody without being aVected by the HIER buVer pH value. For antigens containing DNA-binding domains, it may be eVective to use DNAse as pre-treatment in combination with HIER for IHC (Ye et al 2007). …”
Section: Fig 3 Neutral Antigen Pi Groupmentioning
confidence: 99%